Business communication essentials - Bovée, Courtland L (Pearson Prentice Hall, 2005)
Includes bibliographical references and index.; Understanding business communication in today's workplace -- Communicating in teams and mastering listening and nonverbal communication skills -- Planning business messages -- Writing business messages -- Completing business messages -- Working with letters, memos, e-mail, and instant messages -- Writing routine messages -- Writing bad-news messages -- Writing persuasive messages -- Understanding and planning business reports and proposals -- Writing and completing reports and proposals -- Preparing and giving oral business presentations -- Searching for employment and preparing employment messages -- Interviewing for employment and following up.